2021
DOI: 10.3389/fneur.2021.651465
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Coils in Conjunction With the Pipeline Flex Embolization Device for the Treatment of Cerebral Aneurysms

Abstract: Background: Flow diverters (FD) have shown promising results in the treatment of intracranial aneurysms (IAs). However, there is still controversy whether pipeline flex embolization device (PED flex)-assisted coils can facilitate the curing of aneurysms. Our aim was to assess the safety and effectiveness of PED flex adjunctive with coils (PED flex + coil) in the treatment of IAs.Method: Patients who underwent PED flex treatment in combination with coiling between January 2018 and June 2020 were included in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…Third, coils adjunctive with PED are complementary, rather than competing, for cerebral aneurysm treatment ( 17 ). In a recent single-center study ( 18 ), with a very small subset of the same patients as the present study, it was reported that pipeline-assisted coiling increased the complete occlusion rate without increasing surgical complication rate. In terms of results, the surgical strategy we selected had similar results to the PREMIER study, which was more in line with China's national conditions.…”
Section: Discussionmentioning
confidence: 48%
“…Third, coils adjunctive with PED are complementary, rather than competing, for cerebral aneurysm treatment ( 17 ). In a recent single-center study ( 18 ), with a very small subset of the same patients as the present study, it was reported that pipeline-assisted coiling increased the complete occlusion rate without increasing surgical complication rate. In terms of results, the surgical strategy we selected had similar results to the PREMIER study, which was more in line with China's national conditions.…”
Section: Discussionmentioning
confidence: 48%
“…Zhang et al compared 99 aneurysms with a pipeline embolization device (PED) and 41 aneurysms with PED combined with coiling. In these cases, the adjunctive coil embolization group obtained higher satisfactory angiography results (92.7 vs. 78.8%, P = 0.047) without increasing any periprocedural complications ( 22 ).…”
Section: Discussionmentioning
confidence: 92%
“…First, adjunctive coil embolization with the flow diversion technique can promote thrombus formation in the aneurysmal sac, thereby achieving a higher complete occlusion rate and preventing aneurysm rupture ( 25 ). Second, the change in flow hemodynamics caused by the deployment of coils can contribute to neointimal hyperplasia formation across the device construct and aneurysm orifice ( 22 ). Notably, the deployment of coils affects stent visibility and increases the complexity of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, coils within the aneurysm dome can prevent possible herniation of the PED device into the aneurysm cavity. An increased aneurysm occlusion rate has been demonstrated in patients with cerebral aneurysms which had been treated with the PED device plus coils 37 . At six month-follow-up of patients with cerebral aneurysms treated with the PED device with or without coiling, the complete occlusion rate of aneurysms was 85.4% vs 71.7% for aneurysms treated with the PED device plus coils versus the PED device only 37 .…”
Section: Discussionmentioning
confidence: 99%